Kontribusi Aliran dan Organisasi Islam di Indonesia Bagi Pengembangan Pendidikan - Masyath, Khassan; Muslimin, Muhammad Saiful Hidayatul; Awaliyah, Avinda Putri; Indratno, Kreista Sreshi; Azzahra, Fida Uswah; Asdiqoh, Siti (Innovative: Journal Of Social Science Research, 2024)
Islamic sects and organizations have an important role in the development of education in Indonesia. This article aims to research further about what and how the main contributions of Islamic sects and organizations are related to education in Indonesia. Research methods used is a literature study by reviewing several journals and Literary sources related to the topic of discussion This article is then carefully analyzed regarding the contribution of Islamic sects and organizations in Indonesia to the development of education. Focus of the material This article discusses sects in Indonesia, namely Syiah and Sunni and mass organizations in Indonesia, namely Muhammadiyah, Nadhlatul Ulama', LDII. Their contributions are important in advancing Indonesia's education system and shaping a better educational future.